Risk leveling in business environments: A novel approach for macro risk management - Shahid Rasheed; Changfeng Wang; Faiza Yaqub; Suhail Memon (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this study is to presents a structured risk management methodology for managing and controlling the risks in the macro business environments. This paper emphasizes to achieve risk settled environments for industry/ business growth. Design/methodology/approach: In this paper, we present an approach called "Risk Leveling" which signifies both a concept and a methodology; it helps to manage risks in the macro business environments. Risk Leveling follows a multi-tier approach towards divergent risks and focuses on balancing the risky macro environs for better industry/ business settings. It recommends the utilization of the available resources in a systematic and efficient way for risk mitigation; such intent is pursued though a structured procedure which urges to reduce the risks to match them with the risk tolerance of the enterprises; it also attempts to diminish the mutual risk disparities giving rise a context in which no risk is seen too big or too small comparative to the others. The Risk Leveling process utilizes logical tools (e.g. AHP, ALARP etc.) and mechanisms to reach the risk settled environments. Findings: Risk Leveling procedure adopted in the study moves through the standard risk management course and tends to pacify the macro risks to achieve risk settled environments for the industry. It suggests exploiting the mitigation efforts in a balanced and efficient way to conserve the resources. Originality/value: The regimes can practice it to pacify and regulate the macro risk forces in the designated industry/ market segments.
Keywords: 650; Risk Management; Macro Risks; Business Environments; Risk Leveling; Structured Methodology